A comparison formula for residue currents - Lärkäng, Richard (MATHEMATICA SCANDINAVICA, 2019)
Given two ideals I and J of holomorphic functions such that I J, we describe a comparison formula relating the Andersson-Wulcan currents of I and J. More generally, this comparison formula holds for residue currents associated to two generically exact Hermitian complexes together with a morphism between the complexes. One application of the comparison formula is a generalization of the transformation law for Coleff-Herrera products to Andersson-Wulcan currents of Cohen-Macaulay ideals. We also use it to give an analytic proof by means of residue currents of theorems of Hickel, Vasconcelos and Wiebe related to the Jacobian ideal of a holomorphic mapping.